A clinical case of the effective combined use of BCL-2 and PI3K inhibitors in the treatment of a patient with an unfavorable chronic lymphocytic leukemia with transformation into diffuse large B-cell lymphoma (Richter’s syndrome) - O. A. Rukavitsyn; V. P. Pop; M. V. Drozd; Yu. E. Ryabukhina (Онкогематология, 2022)
Understanding the molecular biological basis of chronic lymphocytic leukemia (CLL) pathogenesis and stratification of patients into risk groups has now led to significant advances in treatment. New targeted drugs with different mechanisms of action (bruton’s tyrosine kinase inhibitors, bCL-2 inhibitors, pI3K inhibitors) have significantly improved the prognosis of high-risk CLL patients. In some CLL cases the nodular tumor component can change to a more aggressive subtype of lymphoma (often diffuse large b-cell) with preservation of the small-cell leukemic component with the CLL phenotype (Richter’s syndrome), usually characterized by rapid progression and poor prognosis. The issue of treatment efficacy in patients with Richter’s syndrome still remains unresolved. The results of new drugs clinical trials are often contradictory and cannot yet be recommended for routine use in clinical practice. The low incidence of Richter’s syndrome, the lack of a unified view of the pathogenesis and therapy approaches make the search for effective drugs an urgent task, so each clinical observation is of undoubted interest.A clinical case of CLL patient with unfavorable molecular cytogenetic risk and transformation into diffuse large b-cell lymphoma (Richter’s syndrome) is presented. The combined use of bCL-2 inhibitors (venetoclax) and pI3K (duvelisib) led to the achievement of partial remission followed by a gradual increase in the positive antitumor effect.